Kinetic Perimetry on Virtual Reality Headset - Terracciano, Rossana; Mascolo, Alice; Venturo, Laura; Guidi, Federica; Vaira, Mariangela; Eandi, Chiara M.; Demarchi, Danilo (IEEE transactions on biomedical circuits and systems, 2023)
Objective : We present a portable automatic kinetic perimeter based on a virtual reality (VR) headset device as an innovative and alternative solution for the screening of clinical visual fields. We compared the performances of our solution with a gold standard perimeter, validating the test on healthy subjects. Methods: The system is composed of an Oculus Quest 2 VR headset with a clicker for participant response feedback. An Android app was designed in Unity to generate moving stimuli along vectors, following a standard Goldmann kinetic perimetry approach. Sensitivity thresholds are obtained by moving centripetally three different targets (V/4e, IV/1e, III/1e) along 24 or 12 vectors from an area of non-seeing to an area of seeing and then transmitted wirelessly to a PC. A Python real-time algorithm processes the incoming kinetic results and displays the hill of vision in a two-dimensional map (isopter). We involved 21 subjects (5 males and 16 females, age range 22-73 years) for a total of 42 eyes tested with our proposed solution, and results were compared with a Humphrey visual field analyzer to test reproducibility and efficacy. Results: isopters generated with the Oculus headset were in good agreement with those acquired with a commercial device (Pearson's correlation values r > 0.83 for each target). Conclusions: we demonstrate the feasibility of VR kinetic perimetry by comparing performances between our system and a clinically used perimeter in healthy subjects. Significance: proposed device leads the way for a portable and more accessible visual field test, overcoming challenges in current kinetic perimetry practices.